Social Learning During Online Learning? The Case for Japanese Language - Rahmat, Noor Hanim; Abdullah, Nur Anisah Tan; Ahmad, Normah; Sharif, Sarinah; Yean, Choong Pow; Boon, Mohd Hassan Awang (International Journal of Asian Social Science, 2021)
Teaching language was once thought to be only possible to be done face-to-face. The pandemic has changed not only the mode of learning of language for learners, it has also changed the way people view language learning. One good thing that comes out from the pandemic is that people are forced to accommodate online communication. As a result, many have proven that language learning can be done successfully online. This study is done to investigate the perception of learners on their language instructors’ teaching the Japanese language via online. This study is rooted from two main theories -social learning theory and online engagement- to explain the sense of engagement learners perceive. The instrument used is a survey with 24 items and 5 Likert-scale. 433 students responded to the survey. Findings revealed that learners needed positive stimulus to give positive response in learning behaviour. Learners also learnt form modelling their instructors. Finally, they also learn well in an environment where there are supportive peers to help them cope with online engagements. Findings bear interesting implications towards the learning and teaching of language via online.